Regulation of signaling by cooperative assembly formation in mammalian innate immunity signalosomes by molecular mimics. (March 2020) - Nanson, Jeffrey D.; Rahaman, Md. Habibur; Ve, Thomas; Kobe, Bostjan
Highlights: Signaling by cooperative assembly formation (SCAF) is ubiquitous in innate immunity pathways, including inflammasome and Toll-like receptor pathways. SCAF can be regulated by proteins that mimic the signaling components; they can be produced by mammalian cells and pathogens. The mechanisms of SCAF regulation by protein mimics may include capping or incorporating into filamentous assemblies. Abstract: Innate immunity pathways constitute the first line of defense against infections and cellular damage. An emerging concept in these pathways is that signaling involves the formation of finite ( e.g. rings in NLRs) or open-ended higher-order assemblies ( e.g. filamentous assemblies by members of the death-fold family and TIR domains). This signaling by cooperative assembly formation (SCAF) mechanism allows rapid and strongly amplified responses to minute amounts of stimulus. While the characterization of the molecular mechanisms of SCAF has seen rapid progress, little is known about its regulation. One emerging theme involves proteins produced both in host cells and by pathogens that appear to mimic the signaling components. Recently characterized examples involve the capping of the filamentous assemblies formed by caspase-1 CARDs by the CARD-only protein INCA, and those formed by caspase-8 by the DED-containing protein MC159. By contrast, the CARD-only protein ICEBERG and the DED-containing protein cFLIP incorporate into signaling filaments and presumably interfere with proximity based activation of caspases. We review selected examples of SCAF in innate immunity pathways and focus on the current knowledge on signaling component mimics produced by mammalian and pathogen cells and what is known about their mechanisms of action.